Monoculture versus Diversity in Competition Economics - Oliver Budzinski (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2007)
Economics rightfully represents the major basis for competition policy. Next to generating knowledge about competition and its welfare effects, the currently popular more-economic approach is charged with a number of additional hopes and expectations, leading to a reduction of the ambiguities of real-world competition policy. While this article highlights the benefits of economicsbased competition policy, it takes a cautious stance towards excessive expectations in particular regarding the idea that a monocultural, unified competition theory as an exact, objective, and unerring scientific approach to antitrust makes normative assessment and generalizations superfluous. In a combination of two lines of argumentation, diversity in competition economics is advocated. Firstly, competition economics is empirically characterized by a considerable pluralism of theories and policy paradigms. This includes deviating views on core concepts like the nature of competition, the meaning of efficiency, or the goals of antitrust. Secondly, it is demonstrated that diversity of theories represents no imperfection of the state of science. In contrast, it is theoretically beneficial for future scientific progress. Therefore, no ultimate competition theory can ever be expected. As a consequence, the more-economic approach must be extended in order to embrace diversity. This does not decrease its meaning and importance but instead puts some of the related high hopes into perspective.
Keywords: L40; B50; L10; K21; 330; more-economic approach; competition policy paradigms; industrial economics; methodology of science; antitrust